Sector-wise assessment of companies’ severity of taxation in Russian regions - Vylkova Elena (Peter the Great St. Petersburg Polytechnic University, 2021)
At all times, it is important to know how great the tax burden, tax pressure and severity of taxation are for the state, regions, citizens. Since the theoretical interpretation of the named concepts and their computational methods are ambiguous, their systemic identification and calculation is in demand. The purpose of the study is to substantiate the methodology for calculating severity of taxation and fiscal taxation for a company, industry, region, state, as well as to test the proposed methodology for calculating company’s severity of taxation in the regions of the Russian Federation. The research methodology involves the formation of a system of tax indicators; calculation and analysis of turnover severity of taxation in Russian regions by type of activity; interpretation of the results obtained. The study of severity of taxation in 2019 made it possible to identify the most successful regions in tax administration: Moscow, Chukotka Autonomous Okrug, Krasnoyarsk Territory, the Republic of Kalmykia; the Kabardino-Balkarian Republic; Novgorod Oblast. The most problematic territories include the Chechen Republic, Kemerovo Region, the Republic of Dagestan and a number of others. Federal and regional authorities should pay attention to both the listed regions and the types of economic activities with the greatest spread in the values for severity of taxation: mining, agriculture and forestry, hunting and fish farming, information activities, communications and others. In the future, it is advisable to calculate the indicator under study for a number of years; focus on the substantive study of the experience of regions and industries of leaders in severity of taxation in order to replicate their successful experience in tax administration. A promising direction is also the construction of a map of deviations for severity of taxation and the tax burden for the Russian regions from the average Russian, both in general and for specific types of activity. The ratio of fiscal and tax burdens, fiscal and tax pressure, severity of taxation and fiscal taxation deserve a more detailed empirical estimation as well.